2018
DOI: 10.1155/2018/5682078
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Treatment of Metastatic Urothelial Carcinoma

Abstract: Platinum-based combination chemotherapy has been the standard of care in the first-line treatment of metastatic urothelial carcinoma (mUC). Treatment of metastatic disease following progression on platinum-based regimens has evolved significantly in the last few years. Clinical trials are currently ongoing to determine how best to use and sequence these treatments. In this minireview, we will review current first-line treatment options in both cisplatin fit and cisplatin unfit patients and advances in first- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…Historically, platinum‐based chemotherapy regimens have been the standard of care for UC and targeted therapies have not been used extensively in the course of clinical care . Trials of EGFR/ERBB2 TKIs in patients with UC who have tumours positive for RTK expression, but not for activating mutations or without any biomarker selection, have been largely unsuccessful .…”
Section: Discussionmentioning
confidence: 99%
“…Historically, platinum‐based chemotherapy regimens have been the standard of care for UC and targeted therapies have not been used extensively in the course of clinical care . Trials of EGFR/ERBB2 TKIs in patients with UC who have tumours positive for RTK expression, but not for activating mutations or without any biomarker selection, have been largely unsuccessful .…”
Section: Discussionmentioning
confidence: 99%
“…There is a large unmet medical need for exploring the mechanism of BCA metastasis and developing new treatments for BCA patients with progressive disease (Bukhari et al, 2018). In this study, we identified the loss of miR-3127 expression in BCA samples using qRT-PCR assays and the TCGA RNA-sequencing data of human BCA.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment at the non-muscle-invasive stage includes transurethral resection of bladder tumor often followed by intravesical chemotherapy or intravesical bacillus Calmette-Guérin immunotherapy [2]. Approximately 25% of patients with bladder cancer will be diagnosed with muscle-invasive disease [3]. Treatment of muscle-invasive bladder cancer includes surgery (cystectomy) combined with adjuvant or neo-adjuvant cisplatin-based chemotherapy [2], or synchronous chemoradiotherapy as an alternative to cystectomy [4], whereas patients with unresectable, locally advanced disease receive chemotherapy [5].…”
Section: Introductionmentioning
confidence: 99%